Attachment relationships, negative automatic thoughts and psychological problems among late adolescents in Rawalpindi, Pakistan - Irfan, Siddrah (2019)
The foundations for a prospect of a healthy development are established during adolescence. Secure attachment relationships with parents and peer play a significant role in adolescent positive development. However, problems with attachment relationships may result in negative automatic thoughts and psychological problems among adolescents. Nevertheless, the mechanism through which attachment relationships predict psychological problems via negative automatic thoughts has seldom been investigated, specifically in the Pakistani context. Moreover, similar and distinct etiological factors for psychological problems among males and females remain understudied. This study thus, investigated the mediating effect of negative automatic thoughts in the association between attachment relationships (maternal, paternal and peer) and psychological problems (depressive and anxiety symptoms), and the moderating effect of sex among late adolescents in Pakistan. Bowlby’s attachment theory and Beck’s cognitive theory were integrated to understand such mechanism among the study variables. A total of 936 participants (males=423, females=513) aged 17 to 19 were identified from the government colleges of Rawalpindi, Pakistan through multistage cluster sampling. Self-administered questionnaires including the Inventory of Parent and Peer Attachment-Urdu (IPPA-Urdu; Zafar, 2009), Depression, Anxiety, Stress Scale–Urdu (DASS-Urdu; Zafar, 2014), and Automatic Thoughts Questionnaire (ATQ-Urdu: Hashmi, 2012) were used to assess perceptions about attachment relationships, symptoms of depression and anxiety, and level of negative automatic thoughts. The preliminary statistics of the constructs including the means, standard deviations, minimum, maximum, frequencies, correlation and t-test were reported. Structural equation modelling was applied (AMOS-23 software) to test the models illustrating the hypothesised linkages. All the measures were validated through confirmatory factor analysis and measurement model. Results from the present study indicated that the direct and indirect models achieved appropriate goodness-of-fit. Paternal and peer attachment were found to be negatively related to depressive symptoms. In contrast, negative automatic thoughts were positively associated with depressive and anxiety symptoms. Further, maternal, paternal, and peer attachment were all negatively related to negative automatic thoughts. Bootstrap analysis showed that negative automatic thoughts fully mediating the associations of maternal and peer attachment with depressive and anxiety symptoms, paternal attachment with anxiety symptoms, whereas, partially mediated the link between paternal attachment and depressive symptoms. The multi-group analysis demonstrated the moderating effect of sex in the mediation model. Overall, the results show that, for males, paternal and peer attachment play a significant role in determining and maintaining their psychological health. While for females, insecure maternal, paternal and peer attachment trigger negative automatic thoughts, which in turn, bring about psychological problems. The study provides greater insight and understanding of the integration of attachment and cognitive theories. Additionally, the study advances understanding of the role of attachment relationships in the development of positive cognitions during late adolescence and underscores that secure attachment relationships with parents and peer are required for the psychological health of late adolescents in Pakistan. Thus, the findings of this study can be helpful to educator, policy makers, practitioner and clinician to develop better intervention and prevention plan for youngsters. The findings help adolescents and parents to improve mental health by improving their communication and interpersonal relationships.